Hubungan Pengetahuan dan Sikap Ibu Nifas tentang Perawatan Luka Perineum - Nurannisa Fitria Aprianti; Eka Faizaturrahmi (STIKes Hamzar, 2025)
A postpartum mother's knowledge of perineal wound care is crucial in wound healing and preventing infection. The purpose is to find out the relationship between knowledge and attitudes of postpartum mothers about perineal wound care. Type of research Analytical survey with a crosssectional approach, The research location is in the Work Area of the Sukaraja Health Center, the research was conducted in May-June 2025, The population is all postpartum mothers who gave birth in the working area of the Sukaraja Health Center and experienced perineal tears, the sample in this study amounted to 45 postpartum mothers who experienced perineal injuries with accidental sampling techniques. The instrument uses a questionnaire. Test the statistic with a chi-square. The results were obtained that the age of most of the people was 20-35 years old as many as 29 people (64.4%), education was mostly low as many as 23 people (51.1%), work was mostly not working as many as 25 people (55.6%) and parity was mostly primipara as many as 26 people (57.8%), knowledge was mostly lacking as many as 23 people (51.1%) and perineal wound care was mostly not carried out as many as 31 people (68.9%). The chi-square statistical test obtained a value of p=0.000 <0.05, meaning that there is a meaningful relationship between the knowledge and attitude of postpartum mothers about perineal wound care in the work area of the Sukaraja Health Center. To increase the knowledge of postpartum mothers, health workers and health centers must provide educational information on how to properly treat perineal wounds..